A new species of Scytodes from Algeria (Araneae: Scytodidae), with a review of the species from the Maghreb - Keer, Johan Van; Bosmans, Robert (Zootaxa, 2014)
Four spitting spider species in the genus Scytodes are recorded from the Maghreb: Scytodes annulipes Simon, 1907, stat. n. (elevated to species rank), S. major Simon, 1885, S. velutina Heineken & Lowe, 1832 and Scytodes seppoi Bosmans & Van Keer, sp. n. The male and female of the latter are described and illustrated. No recent records of the commonly cited S. thoracica (Latreille, 1804) can be provided, so earlier citations are considered to be erroneous. Images, illustrations and new distribution data of the other three known species in the Maghreb are given.